Atypical and inflexible visual encoding in autism spectrum disorder. - Emily L Isenstein; Woon Ju Park; Duje Tadin (PLoS Biology)
Encoding, which involves translating sensory information into neural representations, is a critical first step in the sensory-perceptual pathway. Using a visual orientation task, a new study found both lower encoding capacity and less flexible adaptation in people with autism spectrum disorder.